2005
DOI: 10.1159/000089268
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Posterior Perforating Ocular Injury in Rabbit Eyes: Effects of Radiotherapy with or without Intravitreal Cyclosporin on Vitreous Proliferation

Abstract: Double perforating ocular injuries were made in 30 rabbits and the effects of radiotherapy (RT) alone or in combination with cyclosporin (CS) on vitreous proliferation investigated. Thirteen rabbits in group 1 received RT alone (600 cGy), and 13 rabbits in group 2 received RT combined with 100 µg of intravitreal CS. No treatment was given to 4 rabbits in the control group (group 3). All animals were ophthalmologically examined on the 1st, 3rd, 7th, 14th and 28th days following the injury and the clinical findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The ultrastructural changes seen on electron microscopy were also less severe. 113 A study by Karakücük et al 114 showed that intravitreal cyclosporine could also be used as an adjuvant to radiotherapy to inhibit intraocular proliferation following penetrating ocular injury in rabbits. Jong et al studied the effect of intramuscular (25 mg/kg) and intravitreal CsA (5 mg) administered before and after the induction of herpes simplex (HSV) uveitis and found that a combination of intramuscular and intravitreal CsA before the induction of uveitis significantly reduced the uveitis.…”
Section: Immunosuppressantsmentioning
confidence: 99%
“…The ultrastructural changes seen on electron microscopy were also less severe. 113 A study by Karakücük et al 114 showed that intravitreal cyclosporine could also be used as an adjuvant to radiotherapy to inhibit intraocular proliferation following penetrating ocular injury in rabbits. Jong et al studied the effect of intramuscular (25 mg/kg) and intravitreal CsA (5 mg) administered before and after the induction of herpes simplex (HSV) uveitis and found that a combination of intramuscular and intravitreal CsA before the induction of uveitis significantly reduced the uveitis.…”
Section: Immunosuppressantsmentioning
confidence: 99%